Relationship Between Family Support and Pregnant Women's Interest in Undergoing PMTCT - 'Ainayatul Akhzami; Nur Azizah Indriastuti (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
HIV/AIDS remains a public health problem in Indonesia due to its serious impact on the health of mothers and infants. The prevention of mother-to-child transmission of HIV can be carried out through the Prevention of Mother to Child Transmission (PMTCT) program. However, the interest of pregnant women in participating in HIV testing within the PMTCT program is still relatively low. This condition is partly influenced by a lack of family support. Family support includes emotional, informational, instrumental, and appraisal support, which play an important role in helping pregnant women make appropriate health-related decisions. This study aims to examine the relationship between family support and the interest of pregnant women in participating in PMTCT. The study employed a quantitative method with a cross-sectional design. The sample consisted of 125 pregnant women selected using purposive sampling according to the inclusion criteria. Data were collected using questionnaires on family support and pregnant women’s interest, which had been tested for validity and reliability. Data analysis was performed using Spearman’s correlation test. The results showed that the majority of respondents had good family support (75.2%) and a high interest in participating in PMTCT (78.4%). Spearman’s rho test indicated a significant relationship between family support and pregnant women’s interest in PMTCT, with a correlation coefficient of r = 0.308 and p < 0.0001. This study demonstrates the role of family in increasing pregnant women’s interest in PMTCT.